PROFIL SIKAP PEDULI LINGKUNGAN SISWA SMA DI ACEH - Silvi Puspa Widya Lubis; Syarifah Rahmiza Muzanna; Inayatul Firdausiyah (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This research is aiming at describing learners’ attitude of caring the environment at SMA Negeri 1 Indrapuri Kabupaten Aceh Besar. Descriptive quantitative is the research method used in this study in the effort of describing learners’ attitude of caring the environment through the use of questionnaire as the research instrument. This questionnaire contains of three indicators, those are (1) maintaining cleanliness and environmental sustainability; (2) planning of environmental damage prevention activities, and (3) managing the natural resources. The results showed that: the attitude of environmental caring by students of class XI SMA Negeri 1 Indrapuri Aceh Besar district is in good category that is 62.87%. The highest value of 69.3% is in the indicator of natural resource management, in the indicator of maintaining cleanliness and environmental sustainability, it shows 60.93% and the lowest value is 58.4% in the indicator of planning for environmental damage prevention activities. It has been proved through the results of the questionnaire that most students choose answers agree. Based on the observations, it can be seen that teachers always encourage students to always maintain the cleanliness of their classroom environment, for example by always throwing trash in their place, giving an appeal to students to always arrange daily class hygiene schedule and doing mutual cooperation routinely.